"After you, my dear Alphonse;" Or, when politeness and good intentions are not enough. Issue 4 (2nd October 2021) - Foster, Frances Smith
ABSTRACT: For a variety of reasons, emerging research areas can excite and often motivate people to explore and even contribute. But too often even for experienced scholars, academic prowess, good intentions, and curiosity are inadequate, even dangerous. Careful analysis of one's own strengths and weaknesses along with fastidious research and contextualization are essential if one's efforts are to produce accurate, complete, and useful scholarship. Targeted collaboration can be the vaccine against miseducation and misinformation.